SPRINGATE S-SCORE MODEL ANALYSIS BEFORE CORPORATE MERGER AND ACQUISITION: A STRATEGY EXECUTION FOR PT. WASKITA KARYA, TBK - Sazly, Syukron; Erri, Dirgahayu; Prana, Indra; Dewi, Intan Kusuma (Univesitas Muhammadiyah Tangerang, 2024)
Financial distress is a situation that leaders and owners of firms want to evade, as it is a precursor to insolvency. This study employed financial ratio data and S-Score values to analyze the financial state of PT.Waskita Karya Tbk from 2019 to 2023. The data demonstrate a notable deterioration in the company's performance throughout that timeframe, with financial challenges commencing in 2019 and intensifying until 2023. The escalating likelihood of bankruptcy is linked to a decline in financial parameters such as efficiency, leverage, liquidity, and profitability, as well as a reduced S-Score. Suggested actions including reassessing the financial strategy, adopting improved debt control measures, formulating a plan for financial recuperation, partnering with financial specialists, and strengthening financial supervision and performance tracking, then merger and acquition with other Stated Owned Enterprises with excellent financial performance such as PT. Hutama Karya could an alternative salvation strategy . By applying these suggestions, organizations are anticipated to enhance their financial situation and mitigate the likelihood of bankruptcy in the future.